Pengaruh Corporate Governance dan Subsequent Event terhadap Audit Report Lag - Ginting, Egina Charista; Elma Muncar Aditya; Nurdhiana (Jurnal Ilmiah Aset, 2025)
Audit report lag is the time period between a company's financial year-end and the date its audited financial statements are released. This study aims to analyze the influence of corporate governance mechanisms and subsequent events on audit report lag. The study was conducted on 36 industrial goods companies listed on the Indonesia Stock Exchange (IDX) for the period 2022 to 2024. The analysis technique used in this study was multiple linear regression analysis. The results of the study indicate that subsequent events and size of the board of directors, have an effect on audit report lag, while independent commissioners, independent audit committees, and auditor opinions, has no effect on audit report lag.